Rheumatology telephone advice line - experience of a Portuguese department - Ferreira, Ricardo Jorge de Oliveira (2015)
Background: Telephone helplines for patients are a tool for information and advice. They can contribute to patient's satisfaction with care and to the effectiveness and safety of treatments. In order to achieve this, they need to be adequately adapted to the target populations, as to incorporate their abilities and expectations. Aims: a) Evaluate the adherence of patients to a telephone helpline managed by nurses in a Portuguese Rheumatology Department, b) Analyse the profile of users and their major needs, c) Analyse the management of calls by the nurses. Material and Methods: The target population of this phone service are the patients treated at Day Care Hospital and Early Arthritis Clinic of our department. Nurses answered phone calls immediately between 8am and 4pm of working days. In the remaining hours messages were recorded on voice mail and answered as soon as possible. Details of the calls were registered in a dedicated sheet and patients were requested permission to use data to improve the service, with respect for their rights of confidentiality, anonymity and freedom of decision. Results: In 18 months 173 calls were made by 79 patients, with a mean age of 47.9 years (sd=9.13). Considering the proportions of men and women in the target population, it was found that men called more frequently (males= 32.7% vs females= 20.4%, p=0.016). The reasons for these calls can be divided into three categories: instrumental help, such as the request for results of complementary tests or rescheduling appointments (43.9% of calls); counselling on side effects or worsening of the disease/pain (31.2 %); counselling on therapy mana gement (24.9%). Neither sex nor patient age were significantly related to these reasons for calling. Nurses resolved autonomously half (50.3%) of the calls and in 79.8% of the cases there was no need for patient referral to other health services. Conclusions: About a quarter of patients adhered to the telephone helpline. Patients called to obtain support in the management of disease and therapy or to report side effects and/or symptom aggravation in addition to reasonable instrumental reasons. This suggests that this service may provide important health gains, in addition to comfort for the patient.